Investigating the impact of governmental governance on megaproject performance: evidence from China - Zhai, Zhao; Shan, Ming; Le, Yun (Technological and Economic Development of Economy, 2020)
Governmental governance is an emerging concept in the area of governance and is critical to the success of megaprojects. The aims of this study are to investigate the impact of governmental governance on megaproject performance and to identify the most critical component of governmental governance. To achieve these goals, a conceptual framework of governmental governance and a comprehensive framework of megaproject performance were established first, followed by proposing a research hypothesis that governmental governance could contribute to megaproject performance. To test the hypothesis, data collected by a questionnaire administered to 239 professionals were analyzed using partial least squares structural equation modelling. Results showed that governmental governance could contribute to megaproject performance significantly. It also reported that “public monitoring and scrutiny” was the most critical latent variable of governmental governance on megaproject performance, followed by “systemic risk management,” “regulatory oversight,” “construction of clean government,” “strategic planning,” and “institutional design.” This study has contributed to the body of knowledge of governmental governance by investigating its impact on megaproject performance. The findings from this study are useful to the industry as well, because they can enhance practitioners’ understanding of governmental governance, which could help them improve their management of megaprojects eventually.